Bioactive effects of Curcumin in human immunodeficiency virus infection along with the most effective isolation techniques and type of nanoformulations - Butnariu, Monica; Quispe, Cristina; Koirala, Niranjan; Khadka, Sujan; Salgado-Castillo, Carla Marina; Muhammad Akram; Rabia Anum; Yeskaliyeva, Balakyz; Cruz-Martins, Natália; Martorell, Miquel; Kumar, Manoj; Bagiu, Radu Vasile; et al. (Dove Medical Press, 2022)
Human immunodeficiency virus (HIV) is one of the leading causes of death worldwide, with African countries being the worst affected by this deadly virus. Curcumin (CUR) is a Curcuma longa-derived polyphenol that has attracted the attention of researchers due to its antimicrobial, anti-inflammatory, antioxidant, immunomodulatory and antiviral effects. CUR also demonstrates anti-HIV effects by acting as a possible inhibitor of gp120 binding, integrase, protease, and topoisomerase II activities, besides also exerting a protective action against HIV-associated diseases. However, its effectiveness is limited due to its poor water solubility, rapid metabolism, and systemic elimination. Nanoformulations have been shown to be useful to enhance curcumin’s bioavailability and its effectiveness as an anti-HIV agent. In this sense, bioactive effects of CUR in HIV infection are carefully reviewed, along with the most effective isolation techniques and type of nanoformulations available.